Synthesis of Pd particles with various shapes by ionic liquids for HFP hydrogenation catalyst - Kim, Chang Soo; Yoo, Kye Sang (Springer Verlag, 2014)
Palladium particles were simply synthesized using various ionic liquids. The morphology of the particles was significantly affected by the anion parts of the ionic liquids. Among the ionic liquids, hexafluorophosphate as an anion part was more effective in forming the palladium particles with relatively small and narrow size distribution. However, irregularly shaped palladium particles were synthesized without ionic liquid assistance. For a hexafluoropropylene hydrogenation to produce hydrofluorocarbons, palladium was impregnated on a carbon powder as a catalyst. During the preparation of the catalyst, ionic liquids were added to control the shape of the palladium on the support. After calcinations at 500 A degrees C, all catalysts possessed the comparable crystal structure. Under identical reaction conditions, the catalyst prepared using 1-hexyl-3-methylimidazolium hexafluorophosphate was the most effective in this reaction. Hence, catalytic activity was mainly determined by the size of the palladium particles.